Reactive surface coating of metallic lithium and its role in rechargeable lithium metal batteries. (20th November 2021) - Samarasingha, Pushpaka B.; Lee, Ming-Tao; Valvo, Mario
Highlights: A protective layer is directly formed on thin Li metal by controlled exposure to O2 . The impact of this protective layer is studied in Li cells with a LiFePO4 cathode. Use of a standard LiPF6 or F-free electrolyte displays different performances. Coupling the protective layer with a F-free electrolyte enables longer cycling. Abstract: Realization of an outermost layer on the surface of metallic lithium is performed via reactive exposure of a thin lithium foil to a constant flow of pure O2 gas in a controlled, airtight environment to form spontaneously a ceramic-type, Li-ion conductive film for use in rechargeable lithium metal batteries with a liquid electrolyte. This layer acts as possible intermediate 'buffer' between the underlying lithium and solid electrolyte interphase (SEI) formed in contact with the electrolyte. The impact of this oxygen-containing layer on the cycle performances of thin lithium anodes and associated surface evolution are studied here in cells having LiFePO4 as stable cathode. The influence of this protective layer on 30 μm-thick lithium metal anodes and related effects on the electrochemical behaviour of corresponding cells are investigated with both standard LiPF6 electrolyte and lithium bis-oxalato-borate (LiBOB) as F-free alternative. Combining lithium oxide coating and LiBOB appears to play a key role in extending cell cycling and hindering dendrite formation, although a clear surface roughening of the cycled lithium is observed too. This protected lithium cycled against LiFePO4 with LiBOB provides good capacity retention at different C-rates, displaying adequate Coulombic and round-trip efficiencies and simultaneously enhancing the number of charge-discharge cycles. Graphical abstract: Image, graphical abstract